Adherence of Gambian Diets to EAT-Lancet Diet Recommendations for Health and Sustainability. (14th June 2022) - Ali, Zakari; Scheelbeek, Pauline; Felix, Jyoti; Jallow, Bakary; Prentice, Andrew; Green, Rosemary
Abstract: Objectives: We assessed deviation of the Gambian diet from the EAT-Lancet guidelines for healthy and sustainable diets and identified leverage points to improve nutritional and planetary health. Methods: We performed secondary analyses using the recent Integrated Household Survey dataset comprising food consumption data from 12, 713 households. Consumption of different food groups were compared against EAT-Lancet reference diet targets to assess deviation from the guidelines. We computed a "sustainable and healthy diet index" based on deviation of different food groups from the EAT-Lancet recommendations and modelled the socio-economic and geographic determinants of households that achieved higher scores on this index, using multivariable mixed effects regression. Results: The average Gambian diet had very low adherence to EAT-Lancet recommendations. The diet was dominated by refined grains and added sugars consumption which exceed the recommendations. Consumption of important food groups such as fruits, vegetables, dairy, poultry, and beef and lamb were much lower than the EAT-Lancet targets. Family characteristics associated with higher healthy and sustainable diet index scores included: being a female headed household, having a relatively small household size, having a schooled head of the household, having a high wealth index, and residing in an urban settlement. Furthermore, seasonality and crop production diversity played an important role in the diet, with healthier and more sustainable diets reported in the dry season as compared to the rainy season, and increased adherence with high crop production diversity. Conclusions: While the Gambian diet may be less healthy, it is low in components known to impact most on the environment such as beef, lamb, dairy, and pork. There are opportunities to improve on healthiness of diets by focussing on the substitution of refined grains by wholegrains and reducing added sugar consumption. Given the important role of poverty, education, and agricultural diversification in dietary quality, it would be important to consider these as an integral part of decision making around dietary sustainability in The Gambia. Funding Sources: Wellcome Trust.